The Compliance of Current Small Animal CPR Practice With RECOVER Guidelines: An Internet-Based Survey - Gillespie, Íde; Fletcher, Daniel J.; Stevenson, Mark A.; Boller, Manuel (Frontiers in Veterinary Science, 2019)
In 2012 the Reassessment Campaign on Veterinary Resuscitation (RECOVER) published evidence-based treatment recommendations for dogs and cats with cardiopulmonary arrest, to optimize the clinical practice of small animal CPR and positively impact outcomes. Six years after the release of these guidelines, we aimed to determine the compliance of small animal veterinary CPR practices with these RECOVER guidelines. To identify current CPR practices in clinically active small animal veterinarians and their awareness of the RECOVER guidelines, we conducted an internet-based survey. Survey invitations were disseminated internationally via veterinary professional organizations and their social media outlets. Questions explored respondent demographics, CPR preparedness, BLS and ALS techniques and awareness of RECOVER guidelines. Responding small animal veterinarians (n=770) in clinical practice were grouped by level of expertise: board-certified specialists (BCS, n=216) and residents (RES, n=69) in anesthesia or ECC, practitioners in emergency (GPE, n=299) or general practice (GPG, n=186). Large disparities in preparedness measures, BLS and ALS techniques emerged among levels of expertise. Only 32% (95% CI: 29-36%) of respondents complied with BLS practice guidelines, varying from 49% (95% CI: 42-55%) of BCS to 15% (95% CI: 10-20%) of GPG. While incompliances in BCS, RES and GPE were predominantly due to knowledge gaps, GPG compliance was in addition compromised by limitations in the resuscitation environment (e.g., defibrillator availability, team size). Those aware of RECOVER guidelines (100% of BCS and RES; 77% of GPE; 35% of GPG) were more likely to comply with recommended preparedness (OR=2.4; 95% CI: 1.2–4.8), BLS (OR=4.5; 95% CI: 2.4-9.0) and ALS techniques (OR=7.8; 95% CI: 2.3-49.1) independent of age, gender, region of practice or level of expertise. We conclude that awareness of RECOVER guidelines is high in specialists and residents, but incomplete among general practitioners. This awareness positively influenced compliance with CPR guidelines, but CPR practices continue to be variable and largely not in agreement with guidelines. A widely accessible educational strategy is required to broadly improve compliance with best practices in small animal CPR.